Pattern formation and the mechanics of a motor-driven filamentous system confined by rigid membranes - Mitsusuke Tarama; Tatsuo Shibata (Physical Review Research, 2022)
Pattern formation and the mechanics of a mixture of actin filaments and myosin motors that is confined by a rigid membrane is investigated. By using a coarse-grained molecular dynamics model, we demonstrate that the competition between the depletion force and the active force of the motors gives rise to actin accumulation in the membrane vicinity. The resulting actomyosin structure exerts pressure on the membrane that, due to nematic alignment of the filaments, converges to a constant for large motor active force. The results are independent of filament length and membrane curvature, indicating the universality of this phenomenon. Thus, this paper proposes a mechanism by which the compounds of the cytoskeleton can self-organize into a higher-order structure.